Pelatihan Editing Video Guru SMK Walisongo Dengan Adobe Premier - Pramono, Basworo Ardi; Guntoro Setiaji, Galet; Rifa i, Ahmad (TEMATIK, 2021)
The development of technology in this modern era is very fast, currently technology has provided many benefits in advancing in various aspects. This development is not only in a matter of years, months or days, but hours, even minutes or seconds, especially in relation to information and communication technology supported by electronic technology. The use of technology by humans to help complete work is a necessity in life. The development of this technology must also be followed by developments in Human Resources (HR). The concept of service will teach vocational teachers who have minimal knowledge in the field of video editing. The video editing training with Adobe Premiere is expected to be a learning tool to create content for the learning of Walisongo Vocational School teachers. This training activity is carried out at the Walisongo Vocational School Lab and is supported by a question and answer session, a practicum module will also be given to each training participant. The purpose of implementing this community service is to increase the creativity of the Walisongo Vocational School teachers who will create learning content for their students. From the implementation of community service, it is hoped that it can improve skills and creativity by using Adobe Premiere software, so that later when they create interactive and interesting learning content, either making videos to be given to students or uploaded on YouTube and they can have an in-depth understanding of multimedia, especially the field. video editing with adobe premiere.